MENGOPTIMALKAN MANAJEMEN KEGIATAN KURIKULER DALAM UPAYA MENINGKATKAN KESEJAHTERAAN MAHASISWA - Mustofa Kemal; Muhammad Husain (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study examines the effectiveness of integrating mindfulness, project-based learning, and empowerment approaches into school curricula to improve students' emotional, social, and psychological well-being. The study aims to evaluate the impact of these strategies in addressing the challenges of academic stress and supporting students' holistic development. The methods used include interviews with school principals, activity observations, and analysis of related documents. Data were collected through structured interviews, participant observation, and literature review. Data analysis suggests that mindfulness practices such as meditation, breathing, and reflection sessions can reduce stress by up to 20%, improve focus, and strengthen emotional regulation. Project-based learning has been shown to improve students' social skills by 30%, with team collaboration and social contribution strengthening empathy and a sense of responsibility. The empowerment approach through interest-based learning increases intrinsic motivation by 30% and students' self-control, supporting academic and non-academic balance. The results show that the integration of these three approaches systematically supports students' development not only academically, but also emotionally, socially, and personally, creating individuals who are more resilient, caring, and connected to their community. The study recommends strengthening teacher training, curriculum flexibility, and outreach to parents to support the overall implementation of the program. The integration of these approaches demonstrates the importance of adaptive curricular management for holistic student well-being.